A integração do Plano Diretor de Iluminação com o e o Plano Diretor: estudo de caso: Cingapura e Putrajaya - Lima, Mariana (2018)
A city landscape and its silhouette should emphasize its nightly identity. The urban lighting Master Plan should be thought together with a conceptual elaboration of the Master Plan to maintain a relationship between a night landscape and a daytime landscape, reading the elements together as whole. This work aims to demonstrate that the Lighting Master Plans should accompany Master Plans. In a first moment it is discussed the new concepts of urban lighting according to the theories of L'Urbanisme Lumiére and the City Beautification. As a case study the Lighting Master Plans of Putrajaya and Singapore are presented which demonstrate their compliance with their respective Master Plans. Both use lighting as a tool for the hierarchy of roads and buildings, emphasize their organic forms and maritime fronts, prioritize pedestrian lighting and use the lighting as an urban marketing tool based on the interests of the market logic reproduction.